THE IMPACT OF MACROECONOMIC VARIABLES ON INDONESIA ISLAMIC BANKS PROFITABILITY - Cupian Amzal (Universitas Airlangga, 2016)
Economic development of Indonesia has an important role in the growth of Islamic banking sector. It is clear that the Islamic banking sector in Indonesia needs a conducive economic situation to make a better performance. The objective of this study was to investigate the influence of macroeconomic variables on the profit of Islamic Banks in Indonesia. Macroeconomic variables used in this study were Gross Domestic Product (GDP), Inflation rate and BI Rate (interest rate of the central bank of Indonesia). In addition, Non Performing Financing (NPF) was included in this model to represent another determinant for banks in gaining profit. Econometric model by formulating a multiple regression model was used to estimate the impact of GDP, BI Rate, Inflation rate and NPF on the profit of Islamic banks.The results of this study showed that partially, all explanatory variables (GDP and BI Rate, Inflation Rate and NPF) have a significant effect on the Profit of Islamic Banks.Keywords: Macroeconomic variables, Islamic banks, Non Performing Financing